PELAKSANAAN PROGRAM CSR PT. CIKARANG LISTRINDO DI DESA SINDANGSARI KECAMATAN SUKASARI KABUPATEN SUMEDANG - Nurwulan, Riany Laila; Gunawan, Uga Pratama (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STISIPOL Candradimuka, 2025)
The CSR program implemented by PT. Cikarang Listrindo in Sindangsari Village focuses on the environmental sector. This program is implemented through collaboration with the West Java Environmental Service and the Community Network Center (CNC) by empowering the community through various activities, such as the development of Taman Kehati, aquaponic cultivation, provision of livestock assistance, and bonsai ornamental plant nurseries. The implementation methods in the activities include identifying community needs, collaborating with stakeholders, implementing Empowerment programs, monitoring and evaluation. In order for the CSR program to run effectively, synergy and cooperation between stakeholders (companies, communities, and government) are needed. This program aims to improve community welfare while maintaining environmental sustainability.